Differential distribution of soluble and complexed forms of prostate‐specific antigen in cyst fluids of women with gross cystic breast disease - Malatesta, Manuela (J Clin Lab Anal, 2001)
Gross cystic breast disease (GCBD) is the most common benign disease of the human female breast, and patients with GCBD have an increased risk of breast cancer. The aim of this study was to evaluate the distribution inside apocrine cells and in breast cyst fluids aspirated from gross cysts of prostate‐specific antigen (PSA) molecular forms, and to correlate the different intracystic PSA profiles to the subpopulations of gross cysts. Type I cysts showed a median value of 0.71 &mgr;g/L of total PSA and 0.32 g/L of ACT, significantly different to that of Type II cysts (Wilcoxon P < 0.001). Although large excesses of ACT were detected in all samples, BCF samples and apocrine cells from Type I gross cysts contained about 70% of free PSA, compared to the higher amounts of complexed PSA found in Type II gross cysts. We demonstrate that in apocrine/secretive Type I breast gross cysts the serine protease PSA was mainly present in its free form, in contrast to a major proportion of complexed PSA found in flattened/transudative Type II cysts. Our results are consistent with the notion that a prolonged exposure of apocrine breast cells lining the Type I gross cysts to the proteolytic activity of PSA could be involved in the etiopathogenesis of GCBD. J. Clin. Lab. Anal. 15:81–86, 2001. © 2001 Wiley‐Liss, Inc.